Computer modeling of yttrium aluminium garnet - Mackevičius, Mažvydas; Ivanauskas, Feliksas; Kareiva, Aivaras (Lietuvos matematikos rinkinys, 2010)
On the basis of a two-dimesional model, we estimate diffusion and reaction rates of the yttrium aluminium garnet synthesis at high temperatures.
Keywords: Yttrium aluminium garnet; synthesis; computer modeling